2017
DOI: 10.1007/s10549-017-4525-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum selenium levels predict survival after breast cancer

Abstract: This study suggests that a selenium level in excess of 64.4 µg//L might be beneficial for women undergoing treatment for breast cancer and that selenium supplementation to achieve this level may favorably impact the outcome. Further studies are needed to confirm this association and to evaluate the impact of selenium supplementation on breast cancer survival among women with low post-diagnostic selenium levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 20 publications
4
44
0
1
Order By: Relevance
“…Perhaps this difference is associated with other environmental factors, including diet, however it seems that MMF evidently decreases serum Se level in younger patients. Low serum selenium (≤ 70 μg/L) is associated with an increased risk of developing breast cancer [20]. Our results showed Se concentrations below 70 μg/L in younger patients using MMF, which is significant for both patients and clinicians, due to the increased risk of cancer development [20,21].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Perhaps this difference is associated with other environmental factors, including diet, however it seems that MMF evidently decreases serum Se level in younger patients. Low serum selenium (≤ 70 μg/L) is associated with an increased risk of developing breast cancer [20]. Our results showed Se concentrations below 70 μg/L in younger patients using MMF, which is significant for both patients and clinicians, due to the increased risk of cancer development [20,21].…”
Section: Discussionmentioning
confidence: 61%
“…Serum selenium, iron, zinc, and copper levels were quantified by inductively coupled mass spectroscopy (ICP-MS NexION 350D, PerkinElmer) using methane to reduce polyatomic interferences, following Lubinski et al [20,21]. Calibration standards were prepared by diluting 10 mg/L Multi-Element Calibration Standard 3 (PerkinElmer Pure Plus, PerkinElmer Life and Analytical Sciences, USA) with a blank reagent consisting of a 0.65% solution of nitric acid (Merck, Germany) and 0.002% Tryton X-100 (PerkinElmer, USA).…”
Section: Element Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic and selenium levels in erythrocytes were quantified by inductively coupled mass spectroscopy (ICP-MS NexION 350D, Perkin Elmer) using methane to reduce polyatomic interferences, previously described by Lubinski et al [16]. Each sample was measured in duplicates in different analytical runs.…”
Section: Elements Assaymentioning
confidence: 99%
“…In contrast, selenium (Se) is a micronutrient of supreme importance for human health. Numerous studies have shown that the deficiency of this element is to be associated with, among others, diseases resulting from reduced immunity [15,16]. Se is believed to be the antioxidant trace element that is important in the biological defense against oxidative damage [17,18].…”
Section: Introductionmentioning
confidence: 99%